2017
DOI: 10.1016/j.smim.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the leukotriene B4-BLT1 and LTB4-BLT2 pathways in asthma

Abstract: For several decades, the leukotriene pathways have been implicated as playing a central role in the pathophysiology of asthma. The presence and elevation of numerous metabolites in the blood, sputum, and bronchoalveolar lavage fluid from asthmatics or experimental animals adds support to this notion. However, targeting of the leukotriene pathways has had, in general, limited success. The single exception in asthma therapy has been targeting of the cysteinyl leukotriene receptor 1, which clinically has proven e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 99 publications
0
51
0
Order By: Relevance
“…BLT1 is the high-affinity receptor for leukotriene B4 expressed on a variety of cell types [114]. In allergen-sensitised and -challenged mice, it was the CD8 + BLT1 + and not the CD8 + BLT1 − T-cell subset that was associated with IL-13-mediated asthma and dependent on LTB4 release from mast cells [115][116][117][118].…”
Section: Tc2 Cells In Human Airway Tissuementioning
confidence: 99%
“…BLT1 is the high-affinity receptor for leukotriene B4 expressed on a variety of cell types [114]. In allergen-sensitised and -challenged mice, it was the CD8 + BLT1 + and not the CD8 + BLT1 − T-cell subset that was associated with IL-13-mediated asthma and dependent on LTB4 release from mast cells [115][116][117][118].…”
Section: Tc2 Cells In Human Airway Tissuementioning
confidence: 99%
“…1,6,7 In addition, mast cells express various receptors that recognize pathogen-secreted molecules. 6,7 Mast cells highly express receptors for lipid mediators, 16,17 (Figure 2). These results are consistent with those of a previous study, which reported that MCP-1/CCL2 stored within the intracellular granules at the resting state is rapidly secreted via exocytosis upon stimulation such as PMA, histamine and forskolin.…”
Section: Discussionmentioning
confidence: 99%
“…16 LTB 4 interacts with both high-affinity (BLT1) and low-affinity receptors (BLT2). 17 Additionally, CysLTs reportedly interact with the CysLT1 (CysLT1R) and CysLT2 receptors (CysLT2R). 16 Previously, we had reported that T vaginalis-secreted LTB 4 induces exocytotic degranulation, migration and IL-8 secretion in mast cells through an LTB 4 receptor, BLT1.…”
mentioning
confidence: 99%
“…Besides CysLTs, another leukotriene, LTB 4 , which does not contain a glutathione moiety, has been implicated in the inflammatory process of asthma (Gelfand, 2017). There are two GPCRs for LTB 4 , leukotriene receptor (BLT 1 ) as the high-affinity receptor and BLT 2 as the low-affinity receptor.…”
Section: Structural Insights Into Drug Actionmentioning
confidence: 99%